Imagination first : unlocking the power of possibility - Liu, Eric.; Noppe-Brandon, Scott; ebrary, Inc. (San Francisco : Jossey-Bass, 2009)
When imagination becomes habit, it can transform your work and your life The best corporations know that innovative thinking is the only competitive advantage that cannot be outsourced. The best schools are those that create cultures of imagination. Now in paperback, Imagination First introduces a wide-variety of individuals who make a habit of imaginative thinking and creative action, offering a set of universal practices that anyone can use to transform their life at work, home, and play. These 28.5 practices will enable anyone to become more imaginative and to teach others to do so.
Includes bibliographical references and index.
Keywords: Imagination; Creative thinking; Originality